Posterior corneal elevation after small incision lenticule extraction for moderate and high myopia - Zhao, Yu; Knorz, Michael C. (PLOS ONE, 2016)
Purpose To investigate the changes of posterior corneal elevation after small incision lenticule extraction (SMILE) for moderate and high myopia. Methods In this prospective study, fifty consecutive eyes of thirty patients (10 male, 20 female) who underwent SMILE for myopia and myopic astigmatism were included. Eyes were divided in two groups based on the preoperative spherical equivalent refraction: high myopia group (32 eyes, range -6.25D to -10.00D) and moderate myopia group (18 eyes, range -3.00D to -6.00D). Posterior corneal surfaces were measured by a Scheimpflug camera (Pentacam, Oculus Germany) preoperatively and 1 month, 3 months, 6 months and 12 months postoperatively. Posterior central elevation (PCE) and posterior mean elevation (PME) at 17 predetermined points in the central-4mm area above the best-fit sphere were analyzed. Results No significant difference in the amount of posterior corneal elevation changes in the high myopia group was noted over time (P = 0.23 and P = 0.94 for PCE and PME, respectively). Similarly, the changes in the moderate myopia group before and after SMILE were not significant either (P = 0.34 and P = 0.40 for PCE and PME). A statistically significant correlation was found between the residual bed thickness and the shift of the PCE in the high myopia group at 12 months postoperatively (r = 0.53, P = 0.01). Conclusions The results of this study suggest that the posterior corneal surface remain stable within one year after SMILE for both moderate and high myopia. The changes of PCE correlate to the residual bed thickness for high myopia. Long-term changes of posterior corneal surface need further investigation.